2021
DOI: 10.1016/j.jclinepi.2021.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing was effective in assisting rapid title and abstract screening when updating systematic reviews

Abstract: Background and Objective: To examine whether the use of natural language processing (NLP) technology is effective in assisting rapid title and abstract screening when updating a systematic review.Study Design: Using the searched literature from a published systematic review, we trained and tested an NLP model that enables rapid title and abstract screening when updating a systematic review. The model was a light gradient boosting machine (LightGBM), an ensemble learning classifier which integrates four pretrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…18,49 Software engineering methods such as Natural Language Processing have been used to screen articles, analyze their content, chart results, and so forth. 65,66 For example, a substantial reduction in screening burden with corresponding time savings could be shown by using an artificial intelligence supported software tool. 67 Although automation may be particularly interesting for the time-critical production of RRs, there is little evidence on the validity of these techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,49 Software engineering methods such as Natural Language Processing have been used to screen articles, analyze their content, chart results, and so forth. 65,66 For example, a substantial reduction in screening burden with corresponding time savings could be shown by using an artificial intelligence supported software tool. 67 Although automation may be particularly interesting for the time-critical production of RRs, there is little evidence on the validity of these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In two other papers, automation techniques are mentioned in the discussion sections, but are not part of the recommendation 18,49 . Software engineering methods such as Natural Language Processing have been used to screen articles, analyze their content, chart results, and so forth 65,66 . For example, a substantial reduction in screening burden with corresponding time savings could be shown by using an artificial intelligence supported software tool 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the established rapid recommendation framework, the unique features of MESERT approach are the inclusion of multi-dimensional evidence appropriate for TCM interventions, systematic synthesis of multi-dimensional evidence, assessment of the strength of causal effects in the synthesized evidence. Novel techniques, such as natural language processing, 12 could help evidence identification and screening and accelerate evidence translation.…”
Section: Developing Rapid Recommendations For Tcm Interventions: the ...mentioning
confidence: 99%
“…As a result, our proposed framework offers procedures to process non-English texts for preparing a searching system in a cold-start situation. Different studies on a recommendation for systematic reviews had a natural language approach with the recent famed deep learning architecture of bidirectional encoder representations from transformers (BERT) [12]. The studies showed that the ensemble learning model increases sensitivity and specificity values.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the deep learning approach is convenient for classifying short texts [6][7][8][9]. However, the possibility of overlapped context needs additional information from word concepts of knowledge base [10] or predefined categories of classification system [11,12].…”
Section: Introductionmentioning
confidence: 99%